CORRELATION BETWEEN SELF REPORT SCALE AND PHYSIOLOGICAL MEASURES OF DENTAL ANESTHESIA ANXIETY IN CHILDREN WHILE LISTENING TO MUSIC - Wibisono, W Latifa; Triani, Rini; Anisyah, Ika; Damayanti, Tri; Hanum, Jatsiyah Z (M-Dental Education and Research Journal, 2025)
Background: Dental anxiety of local anesthesia and extraction was the main reason for children to avoid dental treatment. Music therapy is an alternative approach in reducing the physical and psychological stress of children during visits to the dentist. Objective: To determine and correlate the level of dental anxiety on dental anesthesia procedure in children while listening to music, using psychometric and physiological measures.   Methods: A total of 32 children aged 7-10 years were recruited  from patients presenting to Dental Hospital. Subjects divided randomly into two groups. The first group had dental procedure with music and the other group without music.   Both were asked to choose  FIS (Face Image Scale) and had pulse oximetry examination to measure the level of anxiety before and during treatment.  Results:   Coefficient correlation (0.136) was found between FIS and pulse oximetry, indicated that the correlation between two instruments on children's anxiety levels was positive although not statistically different. . Conclusion: Dental anesthesia anxiety while listening to music was reduced significantly different in both psychometric and physiological measures.